An Unusual Presentation of Idiopathic Lymphatic Cyst of the Thigh - Chairat Burusapat; Sophilak Sringkarawat; Sineenard Thanapurirat; Rapeepat Sapruangthong; Chatchai Pruksapong; Kantang Satayasoontorn (Case Reports in Surgery)
Lymphatic cyst is a collection of lymphatic fluid with an epithelial lining which can either represent lymphatic malformations or may occur after trauma or operation. Idiopathic lymphatic cyst of the thigh in adulthood is extremely rare. We report a case of a 27-year-old Thai female presented with a rapidly growing mass over her right thigh. The magnetic resonance imaging scan demonstrated a well-defined, thin rim, enhancing simple cyst. The cyst disappeared for a few days after aspiration. Completed surgical resection was performed for definitive diagnosis and treatment. Immunohistochemical studies revealed the cell lining was positive for CD34, CD31, and D2-40 and negative for calretinin. To our best knowledge, idiopathic lymphatic cyst of the thigh in young adult has never been reported and should be kept in mind in the patient who presents with abnormal thigh mass.